IBAWAH PENGAJARAN DOSEN: KENANGAN MAHASISWA PRODI PENDIDIKAN BAHASA INGGRIS - Afrida, Nina (MAGISTRA, 2016)
This paper is intended to describe studentsâ experiences during instructional process at EnglishDepartment in STAIN Zawiyah Cotkla Langsa TA 2013/2014. Qualitative applied as an approach in thisresearch. The data were obtained from interview technique to 10 students as the sample of research. Thesample was chosen by accidental sampling. The result showed that the methods used by the lecturers inteaching are not effective. It based on studentsâ answer that they did several activities ,which notshould be done during the class is running. The dominant methods applied by the lecturers are lecturingand Discussion .Keyword : Qualitative, research, activities